Analysis of the Effect of Work Environment and Compensation on Teacher Performance at Yayasan Bina Dharma - Nanik Feriyanti (Privietlab, 2023)
This study aims to examine the effect of work environment and compensation on teacher performance at Yayasan Bina Dharma. The research employs a quantitative approach using primary data collected through questionnaires distributed to 50 teachers. Data analysis was conducted using descriptive statistics and multiple linear regression analysis, supported by classical assumption tests including normality, multicollinearity, and heteroscedasticity. The results show that the work environment has a positive and significant effect on teacher performance. A supportive work environment, particularly good interpersonal relationships among teachers, contributes to improved performance. Compensation also has a positive and significant effect on teacher performance, with timely financial benefits playing an important role in enhancing motivation and productivity. Furthermore, the results indicate that work environment and compensation simultaneously have a significant effect on teacher performance. These findings suggest that improving both organizational conditions and compensation systems is essential to enhance teacher performance. This study contributes to the understanding of human resource management in educational institutions, particularly in optimizing performance through workplace and financial factors.